IMPACT OF GOVERNMENT AGRICULTURAL FINANCING ON NIGERIAN ECONOMY (Journal of the Management Sciences, 2025)
This study examined the impact of government agricultural financing on Nigerian economy. The investigation became necessary as inadequate access to agricultural credit appears to persist in Nigeria, posing a constraint to the optimization of farming activities in the country. The study’s specific objectives were to evaluate the impact of the Agricultural Credit Guarantee Scheme Fund (A.C.G.S.F.) on Real Gross Domestic Product (RGDP) and Balance of Trade (BoT), while controlling for Domestic Capital Formation (D.C.F). The ex-post facto research design was adopted while time series data were collected from the Central Bank of Nigeria’s Statistical Bulletin. Having employed the Autoregressive Distributed Lag (ARDL) model in the data analysis, the test results indicated that government agricultural financing through the A.C.G.S.F., has a long-run positive and significant impact on real gross domestic product in Nigeria for the period of study. The result showed that a 1% increase in the A.C.G.S.F., would yield about 3.3% increases in real gross domestic product in Nigeria. The results also revealed a long-run positive but insignificant impact on balance of trade in Nigeria for the period of study. The study concluded that the A.C.G.S.F if well-articulated, remains the most viable channel for government financing of agriculture in Nigeria. Thus, it was recommended that the Nigerian government should come up with long term agricultural financial development promotion plan. Also, policy measures should be used in stimulating massive and consistent financial investment in the agricultural sector to increase RGDP and balance of trade.
Keywords: Government, Agricultural Credit; A.C.G.S.F; Real Gross Domestic Product; Balance of Trade; Economy